1989
DOI: 10.2527/jas1989.671116x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Beijing Black Hogs to Porcine Somatotropin

Abstract: Somatotropin treatment of U.S-breed finishing hogs improves feed efficiency, growth rate and carcass lean-to-fat ratio. Because Chinese-bred hogs have poorer feed efficiency, growth rate and lean-to-fat ratio than U.S. bred hogs, the characteristics affected by porcine somatotropin (PST) may respond differently to treatment. In the present experiment, Beijing Black finishing hogs (a composite of a local Chinese, Berkshire and Yorkshire breeds) were treated with PST for 28 d from average initial to final weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 1 publication
1
4
1
Order By: Relevance
“…Although sows (0.869 kg/day) and barrows (0.848 kg/day) had a slower rate of gain than boars (0.934 kg/day), pST had no significant effect on the rate of gain attained by any group of animals in this experiment. This is in contrast with results documented by earlier investigators who generally reported an increase in ADG (Campbell et al, 1989;McLaughlin et al, 1989). This response was, however, further noted to be dose dependent (Fabry et al, 1991;Klindt et al, 1995) with the former author noting some responses only at 6 mg per day.…”
Section: Resultscontrasting
confidence: 87%
“…Although sows (0.869 kg/day) and barrows (0.848 kg/day) had a slower rate of gain than boars (0.934 kg/day), pST had no significant effect on the rate of gain attained by any group of animals in this experiment. This is in contrast with results documented by earlier investigators who generally reported an increase in ADG (Campbell et al, 1989;McLaughlin et al, 1989). This response was, however, further noted to be dose dependent (Fabry et al, 1991;Klindt et al, 1995) with the former author noting some responses only at 6 mg per day.…”
Section: Resultscontrasting
confidence: 87%
“…Results of these experiments confirmed previous observations that chronic daily injections of porcine somatotropin into growing pigs increased growth rate, lowered F/G, reduced backfat thickness (Campbell et al, 1988(Campbell et al, , 1989McLaughlin et al, 1989;Smith and Kason, 1990) and increased plasma concentrations of IGF-I (Walton and Etherton, 1989; Smith and Kasson, 1990). Also, our results showed that somatotropin-induced growth performance of pigs was related to concentrations of dietary CP.…”
Section: Dlscussionsupporting
confidence: 87%
“…The efficiency of pST effects depend on several factors such as sex, age, breed and environment. It has little effect in fast growing, lean animals (46), but the effect is more pro-6 nounced in Chinese breeds with a higher fat content (47). The metabolic effects are also enhanced in females and in castrated males if compared to intact males, which have a faster growth rate, a lower daily fat deposition and a higher endogenous production of anabolic sex hormones (48).…”
Section: Growth Hormonementioning
confidence: 99%